2007
DOI: 10.3402/ijch.v66i2.18244
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection among non-Native educators in Alaska

Abstract: Objectives. To determine seroprevalence of H. pylori infection in non-Native educators residing in urban or rural settings in Alaska, and to determine potential risk factors associated with infection in this population. Study design. A cross-sectional survey of non-Native educators residing in urban or rural settings in Alaska. Methods. Participants completed a questionnaire detailing aspects of residential life; H. pylori antibody status was determined by a commercial assay. Results. Of the 203 non-Native par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
15
1
1
Order By: Relevance
“…We know of only one study investigating the prevalence of H. pylori infection in non-Native Alaskans. Those authors found an H. pylori seroprevalence of 24% in non-Native school teachers who were living in rural Alaska and were predominantly Caucasian persons born in the contiguous 48 U.S. states; testing for pathogenic genes was not performed in that study (27). In Alaska Native persons, the H. pylori seroprevalence is more than three times higher than what was found in that study (35).…”
Section: Discussioncontrasting
confidence: 51%
“…We know of only one study investigating the prevalence of H. pylori infection in non-Native Alaskans. Those authors found an H. pylori seroprevalence of 24% in non-Native school teachers who were living in rural Alaska and were predominantly Caucasian persons born in the contiguous 48 U.S. states; testing for pathogenic genes was not performed in that study (27). In Alaska Native persons, the H. pylori seroprevalence is more than three times higher than what was found in that study (35).…”
Section: Discussioncontrasting
confidence: 51%
“…Limiting the analysis to studies that adjusted for confounders in children showed a significantly increased likelihood of anemia by 26%: OR 1.26 (95% CI 1.02–1.55), with significant heterogeneity among the studies (Pv=.02). Such association was not observed when combining results of studies of adults (OR 0.95, 95% CI 0.70–1.27).…”
Section: Resultsmentioning
confidence: 90%
“…The 44 studies that scored 12 points or less in the quality assessment score were therefore excluded from the meta‐analysis. Fifty observational studies addressed the outcomes IDA, ID, and/or anemia and met inclusion criteria (Table ) . These studies varied in their design, study population, and method of detecting H. pylori infection; in their classification of IDA, ID, and/or anemia; and in their findings (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations